Home Nasogastric Feeds: Feeding Status and Growth Outcomes in a Pediatric Population. (March 2016) - Rosen, Danya; Schneider, Rachael; Bao, Ruijun; Burke, Patrice; Ceballos, Clare; Hoffstadter-Thal, Kathy; Benkov, Keith
Background: Home enteral nutrition (HEN) is a safe method for providing nutrition to children with chronic diseases. Advantages of HEN include shorter hospitalizations, lower cost, and decreased risk of malnutrition-associated complications. Follow-up after hospital discharge on HEN is limited. The purpose of this study was to look at children discharged on nasogastric (NG) feeds to assess follow-up feeding status and impact on growth. Methods: A retrospective chart review was conducted of pediatric patients discharged from Mount Sinai Medical Center on NG feeds between January 2010 and March 2013. Results: A total of 87 patients were included. Average age was 1.2 years. The most common diagnoses were congenital heart disease (47%), metabolic disease (17%), neurologic impairment (10%), liver disease (9%), prematurity (8%), and inflammatory bowel disease (6%). At most recent follow-up, 44 (50.6%) were on full oral feeds, 8 (9.2%) were still on NG feeds, 9 (10.3%) had a gastrostomy tube placed, 9 (10.3%) were deceased, and 17 (19.5%) had transferred care or were lost to follow-up. Average time to discontinuation of NG feeds was 4.8 months. Change in body mass index from hospital discharge to follow-up visit 6 to 12 weeks after discharge was statistically significant, from a mean (SD) of 13.78 (2.82) to 14.58 (2.1) ( P = .02). Change in weight z score was significant for neurologic impairment (−1.35 to −0.04; P = .03). Height z score change was significant for prematurity (−3.84 to −3.34; P = .02). There was no significant change in height or weight z scores for the other diagnoses. Conclusions: NG feeds can help to improve short-term growth after hospital discharge in children with chronic illnesses.